Pengaruh Islamic Values Dan Corporate governance Terhadap Corporate Governance Disclosure Pada Bank Syariah di Indonesia - Hasanah, Koriatul; Uzliawati, Lia; Lestari, Tri (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to determine the effect of Islamic values and corporate governance on corporate governance disclosure. The independent variables in this research are Islamic values and corporate governance, which are proxied by corporate governance mechanisms, managerial ownership, and institutional ownership. The dependent variable in this research is corporate governance disclosure. This research's population consists of all Annual Reports of Islamic Commercial Banks that are registered with the Financial Services Authority (OJK). The sampling method used was purposive sampling, and 13 companies were selected from a total sample of 52 research data points. The analysis technique used is multiple linear regression with SPSS v25 software. The results of this research indicate that Islamic values have no effect on corporate governance disclosure, corporate governance proxied by corporate governance mechanisms has an effect on corporate governance disclosures, managerial ownership has no effect on corporate governance disclosures, and institutional ownership has no effect on corporate governance disclosures.